The Use of Google Classroom to Teach Writing at Ivet University - Wibowo, Rahmat Ari (Marine Science and Technology Journal, 2023)
This study has a purpose to investigate the implementation of google classroom to teach writing and the cadet’s opinions about the writing instruction through google classroom. This was a descriptive qualitative study that used interviews and questionnaires to collect the data. The sample of this study was the cadets of ship mechanical engineering of Ivet University in the academic year 2022/2023. The results of interviews and the results of cadet’s questionnaires were collected and then analyzed descriptively. The result of this study indicated that 1) the cadets at Ship mechanical engineering conducted several steps in implementing google classroom to teach writing, including opening the class, conducting a main activity, conducting an assessment, closing the lesson, and conducting follow-up activities, 2) the cadets had positive opinions about writing instruction that was implemented through google classroom.